Mixed invasive ductal and lobular carcinoma of the breast: prognosis and the importance of histologic grade - Metzger-Filho, Otto (2022)
© AlphaMed Press 2018. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)